2017
DOI: 10.12816/0039060
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin as a Diagnostic and Prognostic Marker of Sepsis in Critically Ill Patients in Intensive Care Unit

Abstract: Background: Sepsis is a leading cause of mortality in critically ill patients. However, differentiating sepsis from non-infectious triggers of the systemic inflammatory response syndrome (SIRS) is difficult. Procalcitonin is useful biomarker of systemic inflammatory response to infection. Its level rises in response to a proinflammatory stimulus, especially of bacterial origin and not rise significantly with viral or non infectious inflammation. Objectives: The aim of this study was to determine the relation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Univariate Cox regression analysis also manifested that PCT and CRP might be risk factors for the poor prognosis of patients with sepsis. Studies of Savva et al ( 19 ), and Ashour et al ( 20 ) proved that soluble triggering receptor expressed on myeloid cells 1 (sTREM-1) and PCT have very good effects in assessing the severity of sepsis. Currently, there is little research on the value of CRP in assessing the severity of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Univariate Cox regression analysis also manifested that PCT and CRP might be risk factors for the poor prognosis of patients with sepsis. Studies of Savva et al ( 19 ), and Ashour et al ( 20 ) proved that soluble triggering receptor expressed on myeloid cells 1 (sTREM-1) and PCT have very good effects in assessing the severity of sepsis. Currently, there is little research on the value of CRP in assessing the severity of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the previous study George et al, 2015 [19] who found that frequency of adverse outcome was (58/174, 33.3%), while the frequency of prolonged QTc among cases with favorable prognosis (25/116, 46.6%) and cases with adverse prognosis (27/58, 21.6%). Moreover, depending on Ashour et al, 2017 [20] who found that frequency of mortality (18/42, 42.9%), while procalcitonin among non-survivors and survivors 8.20 ± 2.17 and 4.54 ± 1.91 respectively. Assuming the power = 0.80 and α = 0.05, and by using PASS 11 th release the minimal sample size for s single group cohort is 120 cases [21].…”
Section: Sample Size Justificationmentioning
confidence: 95%